Second language learning designs in online adult education - Bergdahl, Nina (Computer assisted language learning, 2025)
Current approaches to assessing digital competence in education may be too broad to support teachers in developing their online learning designs in specific subjects. During the pandemic, studies have identified that the development of teaching practices (and subsequently their learning designs) has taken a leap. However, because digital cultures differ between schools, local approaches need to survey how their practices have developed and what emerging practices can become good examples for others. Using a descriptive multiple case (n = 20) study methodology with observations, interviews (n = 33), and a survey, 12 elements in second language online learning designs (LDs) that seemed to engage learners and support online learning were identified. Data were analysed using pattern matching and descriptive statistics. Post observation, teachers were asked to rate the importance of the ability to include the element and how difficult they perceived its implementation would be. A case overview was used to contrast the survey. Results reveal that the number of digital technologies has little to do with the complexity of designs, and teachers with relatively few digital resources can offer more complex LDs. While most teachers rated the elements suggested as easy, the observations did not support this. However, around 30% of the teachers rated at least seven important elements as difficult or very difficult and designing learning activities that stimulate engagement in nuanced ways was considered challenging. This paper proposes that, identifying local elements may be a suitable way forward to support professional development, as well as to reframe teachers' digital practices post Covid-19.